Re-visiting Mr. Nice: on organized crime as conversational interaction - Van Calster, Patrick (Crime, law and social change, 2006)
Studies of organized crime often seem to have focus almost exclusively on its functionality and rationality. Many researchers tend to construct organized crime as an object, and then to find relations between ‘it’ and its environment. The focus then is on organized crime as a goal-driven object. This view holds that success in crime depends on the roles and tasks people assume. It equates success in crime with functional secrecy and obedience, and therefore with stability. Researchers are seldom interested in everyday, informal elements and events such as coincidental encounters that may occur in everyday life, or personal relationships which have no direct connection with criminal activities. Inspired by the work of Watts and Strogatz [84] and Stuart Kauffman [38, 39], this paper attempts to suggest a complementary perspective on organized crime. The focus here is on the messiness and unpredictability of everyday relations and interactions. This paper illustrates the usefulness of this alternative perspective through a re-reading of Howard Marks’ ego-document which was analysed earlier by Carlo Morselli in his work on network dynamics and criminal career opportunities.